The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.3390/cryst11050563
|View full text |Cite
|
Sign up to set email alerts
|

Surface Enhanced Infrared Absorption Studies of SiO2–TiO2–Ag Nanofibers: Effect of Silver Electrodeposition Time on the Amplification of Signals

Abstract: Surface Enhanced on Infrared Absorption (SEIRAS) and Raman Spectroscopy (SERS) are nondestructive analytic techniques used to detect low concentrations and recognize the fingerprints of molecules. The recognition of the absorption from samples by conventional infrared spectroscopy (IR) via Attenuated Total Reflection (ATR) is difficult for molecules with a low signal strength. However, developed structures with SERS and SEIRAS effect present problems such as high cost, low stability, and low compatibility. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
2
2
0
Order By: Relevance
“…The peaks at 793 and 1020 cm −1 correspond to the asymmetric vibration mode and symmetric stretching mode of the SiO 2 groups (OSiO), respectively. This result is similar to that of the absorption band reported by Abello‐Ribota et al 43 . The peak at 950 cm −1 is attributed to the presence of asymmetric vibration of SiH bond.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The peaks at 793 and 1020 cm −1 correspond to the asymmetric vibration mode and symmetric stretching mode of the SiO 2 groups (OSiO), respectively. This result is similar to that of the absorption band reported by Abello‐Ribota et al 43 . The peak at 950 cm −1 is attributed to the presence of asymmetric vibration of SiH bond.…”
Section: Resultssupporting
confidence: 91%
“…The peaks at 793 and 1020 cm −1 correspond to the asymmetric vibration mode and symmetric stretching mode of the SiO 2 groups (O Si O), respectively. This result is similar to that of the absorption band reported by Abello-Ribota et al 43 The peak at 950 cm −1 is attributed to the presence of asymmetric vibration of Si H bond. The presence of a peak at 1640 cm −1 is attributed to bending of O H groups of SiO 2 (H bonding) of adsorbed water which is based on the scissor bending vibration of water molecules.…”
Section: Ftir Spectroscopysupporting
confidence: 91%
“…27 Others have suggested that weak interactions occur between silver and pyridine and pyridine and water when in solution, and that this can contribute to the EM enhancement of pyridine. 28 Thus, since the material has an enhancement capacity up to 10, 6 it is possible that the pyridine signal is both enhanced by the charge transfer mechanism and the electromagnetic mechanism. Considering the nature of the ceramic substrate obtained from this research, there is a strong possibility that phonon resonance could also be responsible for the enhancement capabilities as some studies have proven the amplifying capacity of Al 2 O 3 -based materials.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Integration of ceramic nanofibers in spectroscopic enhancement substrates has been previously studied, where SiO 2 –TiO 2 , and SiO 2 –hydroxyapatite nanofibers were capable of amplifying IR spectroscopic signals with an enhancement factor of up to 2 × 10, , showing promising results regarding a universal substrate capable of amplifying and being reusable, potentially lowering costs and waste. Other uses of ceramics include, for example, substrates composed of TiO 2 , Ag, and ZnO, capable of both amplifying and photocatalysis making the substrate reusable .…”
Section: Introductionmentioning
confidence: 99%